Factors associated to mothers’ behaviors in dealing with diarrhea among toddlers in South Atambua - Nusantara, Putri Intan Permata; Sirait, Rina Wati; Sir, Amelya B (Jurnal Cakrawala Promkes, 2024)
Diarrhea can be treated properly to reduce its severity. Behavioral elements within society are risk factors that can lead to diarrheal disease. Poor sanitation practices, inadequate access to clean water, improper food handling, and insufficient hygiene habits can increase the risk of transmission of diarrheal illness. Additionally, socio-economic disparities, cultural beliefs, and educational levels can influence individuals' behaviors related to hygiene and sanitation, further exacerbating the risk of diarrheal diseases. Compared to other Puskesmas, the one in South Atambua had a very high number of diarrhea cases in 2021—up to 88 incidents among toddlers, according to Belu District Health Office statistics. This study aimed to identify variables associated with mothers' conduct when treating their toddler's diarrhea. This kind of cross-sectional, quantitative study was carried out in Atambua Selatan, employing a sample size of 72 participants and a simple random sampling technique. The Chi-Square statistical test was utilized in both univariate and bivariate data analysis. The findings indicated that while education level had no association with mothers' behavior in managing the incidence of diarrhea among newborns, knowledge and family support did (p-value = 0.000) have a relationship with maternal behavior in handling diarrhea in toddlers. Otherwise, mothers' behaviors regarding diarrhea among toddlers were not correlated with their level of education. In the future, health officers are expected to provide information on how to deal with diarrhea among toddlers regularly and involve other family members to support mothers. The collaborative efforts of health officers and family members are essential in safeguarding toddlers' health and well-being during diarrhea episodes.